Low seroprevalence of equine piroplasmosis in horses exported from the Netherlands between 2015 and 2021 - Graham, Heather; van Kalsbeek, Paul; van der Goot, Jeanet; Koene, Miriam G. J. (Frontiers in Veterinary Science, 2022)
Equine piroplasmosis (EP) is a tick-borne disease affecting horses, donkeys, mules and zebras, caused by the intraerythrocytic protozoa Babesia caballi and Theileria equi. The geographical distribution of EP is closely related to the distribution of its vectors: tick species belonging to the genera of Dermacentor, Rhipicephalus and Hyalomma. Since the discovery of Dermacentor reticulatus ticks in 2007 and the first reported autochthonous cases in the South of the Netherlands in 2012, no data on the (sero)prevalence of EP in horses in the Netherlands have been reported and it remains unclear whether B. caballi and T. equi have been able to establish themselves in the Netherlands. This study aims to give an update on the current status of EP in horses in the Netherlands using data from serological tests performed in the context of export and screening of 12,881 horses from 2015 through 2020. Horses were categorized as ‘Dutch’, ‘Foreign’ or ‘Unknown’ based on microchip number. The overall seroprevalence of EP in Dutch horses was found to be 0.5% (95% exact CI [0.4-0.7]), compared to 1.9% (95% exact CI [1.3-2.6]) in horses in the category ‘Foreign’ and 1.7% (95% exact CI [1.2 -2.3]) in horses in the category ‘Unknown’. In addition, the seroprevalence per country in the category ‘Foreign’ ranged from 0% (0.95% exact CI [0-2.8]) for Ireland to 6.0% (0.95% exact CI [3.5-9.3] for Spain. In light of the reports on the seroprevalence during the outbreak of autochthonous EP reported in 2012 and on seroprevalences of EP in other countries in Northwestern Europe, the seroprevalence of EP in the Netherlands is very low. However, the higher seroprevalence of EP in horses from abroad warrants the need for the monitoring of EP, as tick vectors are present in the Netherlands and the import of horses from endemic areas increases the chances of EP becoming more prevalent in the Netherlands.